Section 337 and the Protection of Intellectual Property in the United States: The Complainants and the Impact - Mutti, John; Yeung, Bernard (The Review of Economics and Statistics, 1996)
John Mutti, Bernard Yeung, Section 337 and the Protection of Intellectual Property in the United States: The Complainants and the Impact, The Review of Economics and Statistics, Vol. 78, No. 3 (Aug., 1996), pp. 510-520